The negative emotional experiences of women trafficked across borders: Evidence in Vietnam - Truong, Vu Vuong; Ha, Luu Song; My, Trinh Ha (CENTRAL ASIA AND THE CAUCASUS, 2021)
The study was conducted in 2021 in 5 provinces in Vietnam to describe the negative emotional experiences of women trafficked across the border and some related factors. A cross-sectional descriptive study with a quantitative design on 470 trafficked women. Information on the negative emotional experiences of trafficked women and some related factors was collected through personal questionnaire interviews at the clubs and places of residence of these women. Research results show that women trafficked across borders had negative emotional experiences when being trafficked such as insecurity, helplessness, depression, loss, pessimism, disappointment, confusion, and fear. sad. Among them, sadness is the emotion that these women feel the most and the least bewilderment. Ethnic minority women, who were trafficked across borders in adulthood, trafficked into prostitution, and spent more years living abroad due to trafficking, had negative emotional experiences when trafficked. sell at a higher level. 5 factors have a statistically significant impact on the negative emotional experiences of women trafficked across the border, namely ethnic Kinh women, trafficked in adulthood, trafficked for sexual purposes. education, lived abroad for 1 year or less, and 2 to 5 years as a result of being trafficked. In which, ethnic Kinh women are the most influential factor, the number of years of living abroad due to trafficking is the factor with the weakest effect and inversely, that is, the longer the time of being sold abroad. The longer trafficked women experienced lower levels of negative emotions.